Accuracy of intraoperative estimation of femoral stem anteversion in cementless total hip arthroplasty by using a digital protractor and a spirit level - Anuwat Pongkunakorn; Nawakun Phetpangnga; Narawit Kananai (Journal of Orthopaedic Surgery and Research, 2021)
Abstract Background The femoral component anteversion during surgery is traditionally assessed by a visual assessment of the surgeon and has proven to be imprecise. We sought to determine the accuracy of a digital protractor and a spirit level to measure the stem anteversion during cementless THA. Methods A prospective study was conducted among 107 patients (114 hips) who underwent primary cementless THA via posterolateral approach. A pipe with a spirit level was attached to the tibial tubercle and intermalleolar midpoint. While the leg was held perpendicularly to the floor, stem anteversion was estimated by 3 methods: method A by visual assessment; method B by a digital protractor alone; and method C by a digital protractor combined with a spirit level. The angles were compared with the true anteversion measured by postoperative CT scan. Results The average anteversion by method C (22.8° ± 6.9°, range -2° to 40°) was significantly lower than method A (24.6° ± 5.2°, range 0° to 30°) (p=0.033), but not different from the true anteversion (22.1° ± 8.2°, range -5.4° to 43.1°) (p=0.445). There were no significant differences between method B (23.2° ± 8.2°, range -4° to 45°) and method A, C or the true anteversion. The mean deviation of the intraoperative estimation from the true anteversion was 0.8° ± 3.7° (range -7.1° to 8.0°) by method C; 1.2° ± 5.1° (range -8.8° to 14.3°) by method B; and 2.5° ± 7.4° (range -19.0° to 16.0°) by method A. Estimation error within 5° was found in 107 hips (93.9%) with method C; 86 hips (75.4%) with method B; and 59 hips (51.8%) with method A. Conclusion Accurate estimation of stem anteversion during cementless THA can be determined intraoperatively by the use of a digital protractor and a spirit level. Trial registration Thai Clinical Trials Registry ( TCTR 20180326003 ). Registered on 20 March 2018. Retrospectively registered.